2009
DOI: 10.1155/2009/927329
|View full text |Cite
|
Sign up to set email alerts
|

Use of Viscosity to Probe the Interaction of Anionic Surfactants with a Coagulant Protein from Moringa oleifera Seeds

Abstract: The intrinsic viscosity of the coagulant protein was evaluated from the flow times of the protein solutions through a capillary viscometer, and the results suggested the coagulant protein to be globular. The interactions of the coagulant protein with anionic surfactant sodium dodecyl sulphate (SDS) and sodium dodecyl benzene sulfonate (SDBS) were also investigated by capillary viscometry. We conclude that there is strong protein-surfactant interaction at very low surfactant concentrations, and the behavior of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…This effect is clear from the data where the reflectivity is increased and the fringe in the reflectivity is less pronounced. The observed effect of SDS is in agreement with previous physical measurements by Maikokera and Kwaambwa of surface tension [27,28], fluorescence [29], circular dichroism [30] and viscosity [34] when studied as function of SDS surfactant concentration for 0.05 wt% protein solution. All measurements exhibited either maximum or minimum at a critical SDS concentration of about 1 mM.…”
Section: Effect Of Rinsing With Watersupporting
confidence: 91%
“…This effect is clear from the data where the reflectivity is increased and the fringe in the reflectivity is less pronounced. The observed effect of SDS is in agreement with previous physical measurements by Maikokera and Kwaambwa of surface tension [27,28], fluorescence [29], circular dichroism [30] and viscosity [34] when studied as function of SDS surfactant concentration for 0.05 wt% protein solution. All measurements exhibited either maximum or minimum at a critical SDS concentration of about 1 mM.…”
Section: Effect Of Rinsing With Watersupporting
confidence: 91%
“…The data exhibit an increase in surface tension at intermediate SDBS concentrations, with a local maximum occurring at 0.2 mM and 0.768 mM for 0.01% and 0.05%, respectively. It is interesting that the maximum in surface tension profile for 0.05% protein occurs at approximately the same SDBS concentration of 0.768 mM as the maximum observed in the solution viscosity [15].…”
Section: Resultsmentioning
confidence: 78%
“…This is with the view that the protein investigated is used for water treatment and buffer conditions that would not reflect the environment, which is it intended. Furthermore, previous studies have shown that the protein is insensitive up to pH as high as 9 7,8 and the isoelectric point has been reported to be between pH 10 and 11 10 suggesting that it is very stable and to a large extent can be considered as self-buffering.…”
Section: Extraction and Purification Of Proteinmentioning
confidence: 99%
“…3 In our previous work, on the protein from MO seeds, we have used a number of techniques to study effects of these parameters on its properties. The methods of investigation include surface tension, 4,5 fluorescence (intrinsic and extrinsic), 4,6 infrared spectroscopy, 7 circular dichroism (CD), 7 viscosity, 8 and neutron reflection. 9 The intrinsic tryptophan absorbance and fluorescence intensity of MO protein-sodium dodecylsulfate (SDS) solutions were monitored to understand the binding of SDS to MO protein.…”
mentioning
confidence: 99%